Marketing Strategies for Promoting Speech Therapy Services - T. V. Langovaia (Путеводитель предпринимателя)
This article presents a comprehensive study of contemporary approaches to promoting speech therapy services, divided into three main directions: digital platforms, community engagement, and referral systems. The study emphasizes that digital platforms are indispensable in today’s informational activities, considering the growing number of digital opportunities for branding and education these platforms offer. Audience engagement focuses on genuine interaction, connecting to local structures such as schools and media, thereby strengthening brand trust and loyalty. Referral systems, based on professional interdependence, demonstrate the effectiveness of recommendations from both satisfied clients and professional peers. Delving into these strategies, the article consistently underscores the ethical imperatives of marketing in the pedagogical realm. It is asserted that providing genuine value and caring for client well–being should underpin all advertising efforts. In conclusion, this article serves as a comprehensive guide for speech therapists seeking to navigate the intricate realm of modern marketing, offering strategies grounded in authenticity and value delivery.